Partisipasi Politik Perempuan dalam Tinjauan Al-Qur'an dan Hadis - M. Tahir Maloko (AL-Fikr, 2013)
Women and politics has been an interesting subject of discussion not only among political observers and pursuant of women studies, but also among Islamic scientists. The central question raised is to what extent women may undergo opportunities to participate in activities of political nuance. In this context, women’s political participation has become an issue that requires a sound reference in the Quran and Hadith. This is necessary in order to provide flexibility for women to engage in any political activities without being hindered by theological excuses frequently used to hold them back. This paper seeks to present sound reference from the Quran and Hadith as well as additional support structures to see the extent of women’s privilege to participate in politics. Studies of the Qur’an and Hadith show that although some verses of the Qur'an and the Prophetic traditions may seem to suggest certain limitations which brings about impacts on women’s restriction in political sphere, in fact those particular verses and hadith require a further interpretation with regards to social condition contemporary to their time of revelation. At the same time, it was discovered that more verses and prophetic traditions affirm the aspect of equality of men and women to engage in various activities, including those of the politics.